Can Bitcoin be a diversifier, hedge or safe haven tool? Evidence from US markets - [Jiang], [Shuying] (2020)
This dissertation explores Bitcoin’s role as a hedge, safe-haven and a diversifier from a US investor’s perspective using a most recent and a longer time horizon between 2010 and 2019. First, the OLS regression with HAC covariance estimator confirms that most external economic factors do not exert any significant effect on the Bitcoin market returns, which indicates the hedging capability of Bitcoin for risk management. Then the GARCH model with dummy variables and Quantile regression with dummy variables are adopted to examine the hedge and safe-haven capabilities of Bitcoin. The findings show that at the average condition, Bitcoin is a strong hedge against EPU shocks. And in most situations, Bitcoin can act as a weak hedge and weak safe-haven against uncertainty when Bitcoin is in bearish and bullish mood. Finally, Mean-Variance Optimization approach is employed to evaluate Bitcoin’s diversification benefits under four constraining portfolio scenarios. The results show that Bitcoin has the diversification potential should be contained in optimized portfolio. Overall, our findings support that Bitcoin plays an important role in investment management and portfolio diversification, contributing to the constant debate over Bitcoin’s role in investment.